THE ROLE OF LANGUAGE IN THE CONSTRUCTION OF NATIONAL NARRATIVES - Rasulova Diyora Ziyodulla qizi; Abduramanova Diana Valerevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Language plays a pivotal role in shaping and sustaining national narratives, acting as both a tool for communication and a medium for identity construction. This article explores how linguistic choices reflect and reinforce collective memory, shared values, and a sense of belonging within nations. By analyzing historical examples, cultural texts, and political discourse, the study highlights how language is employed to unify diverse populations, legitimize political authority, and frame national ideologies. It also examines the tensions that arise in multilingual or post-colonial contexts, where competing narratives challenge dominant linguistic frameworks. Ultimately, the article underscores the dynamic relationship between language and nation-building, arguing that linguistic practices not only mirror but actively construct the imagined communities at the heart of national identity.